Vpliv kompleksnih interakcij na razvoj sodelovanja v igri javnih dobrin - Duh, Maja (Anali PAZU, 2025)
The emergence and persistence of cooperation among selfish individuals remain one of the most significant challenges that continues to intrigue scientists across various research fields. Evolutionary game theory has become a key tool in these studies, providing a robust theoretical framework to describe the evolutionary dynamics of strategies in social dilemmas. Simultaneously, advances in network science have significantly enhanced our understanding of numerous complex systems in the real world, including the development of cooperation in group decision-making and collective actions. A critical factor in this context is how individuals are embedded within society. Research over the past decades has showed that social network structure critically impacts cooperation. Moreover, as individuals are often mobile in most real-world scenarios, mobility and population mixing also play a crucial role in the evolution of cooperation. The primary aim of our study was to examine how different interaction networks and player mixing influence the evolution of cooperation in the public goods game.
Keywords: complex networks; evolucijska teorija iger; evolutionary game theory; igra javnih dobrin; kompleksna omrežja; Monte Carlo simulacije; Monte Carlo simulations; multilayer networks; public goods game; večplastna omrežja